Invasiveness of pharmacokinetic studies in children: a systematic review - Altamimi, Mohammed; Choonara, Imti; Sammons, Helen (BMJ Publishing Group, 2016)
Objectives: To explore whether pharmacokinetic (PK) studies in paediatric patients are becoming less invasive. This will be evaluated by analysing the number of samples and volume of blood collected for each study within four different decades. Methods: A systematic literature review was performed to identify PK papers describing number of samples and volume of blood collected in studies of children aged 0–18 years. The following databases were searched: MEDLINE (1946 to December 2015), EMBASE (1974 to December 2015), International Pharmaceutical Abstracts (1970 to December 2015), CINAHL and Cochrane Library. Results: A total of 549 studies were identified between 1974 and 2015. There were 52 studies between 1976 and 1985, 105 between 1986 and 1995, 201 between 1996 and 2005 and 191 between 2006 and 2015. The number of blood samples collected per participant increased between the first two decades (p=0.013), but there was a decrease in the number of samples in the subsequent two decades (p=0.044 and p<0.001, respectively). Comparing the first and last decades, there has been no change in the number of blood samples collected. There were no significant differences in volume collected per sample or total volume per child in any of the age groups. There was however a significant difference in the frequency of blood sampling between population PK studies (median 5 (IQR 3–7)) and non-population PK studies (median 8 (IQR 6–10); p=<0.001). Conclusions: The number of blood samples collected for PK studies in children rose in 1985–1995 and subsequently declined. There was no overall change in the volume of blood collected over the 4 decades. The usage of population PK methods reduces the frequency of blood sampling in children.